Aortic Aneurysm (IntechOpen, 2023)
Proper diagnosis and treatment of aortic aneurysm are essential for lowering complication rates in patients suffering from this potentially life-threatening condition. Aortic Aneurysm - Clinical Findings, Diagnostic, Treatment and Special Situations presents a comprehensive overview of aortic aneurysm. With authorship of international acclaim, this comprehensive text is a highly valuable resource for surgeons and trainees.